Prevalence and severity of dental and skeletal fluorosis in a fluoride-endemic region of Karnataka, India - Shilpakala; Jogatappa, Narayana; Kariyajjanvar, Prakash (International Journal Of Community Medicine And Public Health, 2025)
Background: Fluoride contamination in groundwater poses a major public health concern in rural India, where long-term exposure leads to dental and skeletal fluorosis. This study aimed to assess the prevalence and severity of fluorosis in a fluoride-endemic region of Karnataka and to examine its association with demographic factors. Methods: A cross-sectional study was conducted among 246 residents aged 1-90 years in fluoride-affected villages. Dental fluorosis was assessed using the Modified Dean’s Index, while skeletal fluorosis was identified based on clinical symptoms such as back and joint pain, reduced mobility, and difficulty in bending. Groundwater fluoride levels were measured, and statistical analyses, including Chi-square (χ²) tests, were performed to determine associations between variables. Results: Overall, 80.5% of participants exhibited dental fluorosis, of which 30.08% were severe. Skeletal fluorosis was detected in 21.13% of individuals, predominantly among adults aged 41-60 years. A significant association was found between skeletal fluorosis and age (p=0.000), sex (p<0.001), and between dental and skeletal fluorosis (p=0.002). Groundwater fluoride concentrations ranged from 7.9 to 9.5 mg/L, exceeding the WHO permissible limit by more than six times. Conclusions: The study highlights the dual burden of dental and skeletal fluorosis in the region and identifies age- and sex-related vulnerability. Effective community-based awareness, safe water supply interventions, and preventive health strategies are urgently required to mitigate fluoride toxicity and its health impacts in rural populations.